2009
DOI: 10.1021/bi801933c
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Repressor RYBP Is a Natively Unfolded Protein Which Folds upon Binding to DNA

Abstract: RYBP (Ring1A and YY1 binding protein) is a zinc finger protein with an essential role during embryonic development, which binds transcriptional factors, Polycomb products, and mediators of apoptosis, suggesting roles in, apparently, unrelated functions. To investigate mechanisms underlying its association with functionally diverse partners, we set out to study its structural properties using a number of biophysical (fluorescence, circular dichroism, Fourier transform infrared, and NMR spectroscopies) and hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 52 publications
(98 reference statements)
3
37
0
4
Order By: Relevance
“…NUPR1 is not the sole IDP capable of interacting with C-RING1B, because also RYBP protein binds to it (19,20,24,25). The main physicochemical difference between RYBP and NUPR1 is that the former self-associates (both are IDPs, DNA-binding proteins with a high isoelectric point).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NUPR1 is not the sole IDP capable of interacting with C-RING1B, because also RYBP protein binds to it (19,20,24,25). The main physicochemical difference between RYBP and NUPR1 is that the former self-associates (both are IDPs, DNA-binding proteins with a high isoelectric point).…”
Section: Discussionmentioning
confidence: 99%
“…The X-ray structure of the monomers of C-RING1B resembles that of a ubiquitin module, and it serves to interact with CBX proteins (18). Furthermore, we have also shown that C-RING1B is capable of interacting with RING1 and YY1 binding protein (RYBP) (19,20), which is a highly basic, oligomeric, intrinsically disordered protein (IDP) that interacts with DNA (19) and other proteins involved in apoptosis (21-23). The CBX proteins binding to C-RING1B undergo a tightening in their structures (24), and their presence hampers RYBP binding (25).…”
mentioning
confidence: 99%
“…Since the correlation time, s c , is s c % 1 T 2 [13], and, roughly, the M is twice the s c , and thus M can be estimated. Experiments were carried out at 90 and 180 lM of protein concentration, and no variation was observed in the measured T 2 -time (data not shown).…”
Section: Measurements Of the T 2 (Transverse Relaxation Time)mentioning
confidence: 99%
“…Így az úgynevezett "moonlighting" fehérjék családjába tartozik, melyekre jellemző hogy egynél több, egymástól eltérő funkciót képesek ellátni [5]. Ennek megfelelően, az Rybp/DEDAF protein -amellett hogy maga is transzkripciós regulátor és polycomb protein -in vitro kölcsönhatásba lép számos, változatos biológiai funkcióval bíró fehérjével, úgymint DNS kötő (YY1), kromatin módosító (Brg1), proapoptotikus (pro-caspase-8), egyéb polycomb (Ring1A, Ring1B, M33, mPC2) vagy például a sejtek proliferációjában és differenciációjában fontos szabályzó funkcióval bíró Myc-Mad-Max hálózat tagjaival (Mxi1).…”
Section: Az Rybp Fehérje Mint Transzkripciós Regulátorunclassified
“…A két fejérje domén szerkezete is hasonló: azok N-terminális régiót kivéve, ahol a cink-finger domének találhatók, egy szerin-gazdag rész húzódik amely nem mutat homológiát más ismert fehérje doménekkel és nagyfokú rendezetlenséget muatat (IDP; intrinsically disordered proteins) [4,5,9]. …”
Section: Az Rybp Homológ Yaf2 éS Feltételezett Szerepei: a Funkcionálunclassified